Comparison of pulmonary function in isoflurane anaesthetized ventilated sheep (Ovis aries) following administration of intravenous xylazine versus medetomidine. (October 2021) - Raisis, Anthea L; Hosgood, Giselle L; Crawford, Nicholas; Kästner, Sabine; Musk, Gabrielle C; Herrmann, Peter; Mosing, Martina
Alpha2 receptor agonists (alpha2 -agonists) are useful sedative and analgesic agents in sheep, but have adverse pulmonary effects, which are reportedly similar between different alpha2 -agonists. This randomized crossover study compared pulmonary function after intravenous administration of an alpha2 -agonist, either xylazine or an equipotent dose of medetomidine in 34 female sheep anaesthetized twice. Pulmonary function was assessed using spirometry, volumetric capnography, arterial blood gas analysis 1 min prior to, and 5 and 10 min after administration of the allocated alpha 2 agonist drug. Pulmonary structural changes were subsequently assessed using computed tomography (CT). Tachypnoea or hypoxaemia prompted reversal with atipamezole and exclusion of data. Data were analysed for a fixed effect of drug using a mixed effect linear model with significance set at p  < 0.05. Ten sheep administered xylazine required atipamezole while none of sheep receiving medetomidine did. Xylazine produced significantly higher respiratory frequency, airway pressures, airway resistance and arterial carbon dioxide (CO2 ), and lower dynamic compliance, tidal volume, CO2 elimination and end tidal CO2 tension and arterial oxygen tension than medetomidine. This was associated with a significantly lower % of aerated tissue and higher % poorly and non-aerated tissue in CT images of sheep receiving xylazine versus medetomidine. In conclusion, xylazine administration produced marked decreases in pulmonary function, in ventilated isoflurane anaesthetized sheep, when compared to an equipotent dose of medetomidine when administered as an intravenous bolus supporting the use of medetomidine when alpha2 -agonists are required.